Analisis Bahasa Slang dalam Interaksi Virtual pada Platform Game Roblox: Kajian Sosioliungistik: Analysis of Slang in Virtual Interactions on the Roblox Game Platform: A Sociolinguistic Study - Maulida, Zerlina; Pujihastuti, Etin; Riyanton, M. (JBSI: Jurnal Bahasa dan Sastra Indonesia, 2025)
Advances in digital technology have changed the way teenagers communicate, particularly on online gaming platforms like Roblox. This platform has become a platform for the development of slang, a variation of informal language used for quick and efficient communication during gameplay. Slang in online games takes various forms and continues to evolve in response to changing communication needs and trends. The purpose of this study is to describe the forms of slang found in the game "Indo Camp" on Roblox. The method used in this study is a descriptive qualitative approach, with data collected in the form of speech that contains slang. Data were collected through free listening, screen recording, and note-taking techniques. Data analysis employed the matching method, utilizing sorting techniques, determining elements, and comparing and equating methods. The results show the presence of five forms of slang: abbreviations, humorous mispronunciations, shortenings, interjections, and adaptations from foreign languages. Abbreviations dominate, with 12 data points, and interjections are the least common, with 3 data points found out of a total of 31. Slang in online games is temporal, limited, and continues to evolve in response to digital developments and the changing communication needs of teenagers. Online gaming platforms serve as a platform for innovation for teenagers to create and disseminate new terms. This phenomenon also demonstrates adolescent communication patterns in the digital age, demonstrating the linguistic creativity of the younger generation.